Coupled Hydrologic-Mechanical-Damage Analysis and Its Application to Diversion Tunnels of Hydropower Station - Annan Jiang; Xiurong Yang; Mengfei Xu; Tengfei Jiang (Advances in Civil Engineering, 2021)
Since the traditional model cannot sufficiently reflect the multifield coupling problem, this paper established an elastoplastic stress-seepage-damage analysis model considering the seepage field, stress field, and damage field. Simultaneously, the elastoplastic damage model involves many parameters and is difficult to determine. An inverse analysis program is compiled based on the differential evolution algorithm, and the surrounding rock damage parameters are inverted. Finally, the elastoplastic stress-seepage-damage coupling program and the damage parameter displacement back analysis program is compiled using C++ language. Then, the program is used to calculate the coupling problem of tunnel elastoplastic stress-seepage-damage. The results show that the proposed elastoplastic damage constitutive model can well describe the mechanical behavior of rock. The computational procedure can also simulate practical engineering problems, which can provide specific guidance for site construction.